2017
DOI: 10.1016/j.canep.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of a community based participatory research project comparing cytology and urine HPV DNA testing for cervical cancer screening in Yap, Federated States of Micronesia

Abstract: Non-invasive, self-collected sampling methods for HPV DNA detection in women, which are reliable, efficient, and acceptable have the potential to address barriers to cervical cancer screening in underserved communities, including low-middle income countries (LMIC) such as the island nation of the Federated States of Micronesia (FSM). Urine-based HPV testing has not been rigorously evaluated in clinical trials. A pilot community-based participatory randomized control research project evaluated use of urine HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
(14 reference statements)
1
23
0
Order By: Relevance
“…Compared with the growing focus on feasibility studies for randomised clinical trials ( 13 24 ), literature on operational outcomes of observational feasibility studies remains scarce, and restricted to a limited number of measures, such as the overall proportion of invited individuals ultimately participating ( 7 10 ). Few studies have directly assessed measures of sample collection feasibility, with none identified here that specifically examined blood sample collection ( 7 , 25 ). Here, we identified useful indicators relating to various aspects of study operation including sample collection, using these in the context of our study to obtain a clearer understanding of the feasibility of scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the growing focus on feasibility studies for randomised clinical trials ( 13 24 ), literature on operational outcomes of observational feasibility studies remains scarce, and restricted to a limited number of measures, such as the overall proportion of invited individuals ultimately participating ( 7 10 ). Few studies have directly assessed measures of sample collection feasibility, with none identified here that specifically examined blood sample collection ( 7 , 25 ). Here, we identified useful indicators relating to various aspects of study operation including sample collection, using these in the context of our study to obtain a clearer understanding of the feasibility of scale-up.…”
Section: Discussionmentioning
confidence: 99%
“…Community-based organizations.-The involvement of community leaders through community-based organizations was discussed in 80% of the articles. [62][63][64][65][66][67]69,70,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]116,117,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136] The involvement of community-based organizations was cited as a way to leverage, build, and sustain leadership within the Pacific Islander community. 81 Community-based organizations (e.g., federally qualified community health centers and grassroots non-profit community-based organizations) were described as playing a direct role in the research design, study conduct, and dissemination of the results back to the community.…”
Section: Engaging Community Leadersmentioning
confidence: 99%
“…Community advisory board.-More than half (54%) of the reviewed articles mentioned partnering with a community advisory board. 62,[64][65][66][67]69,70,[72][73][74][75][76][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]116,117,[120][121][122][123]…”
Section: Engaging Community Leadersmentioning
confidence: 99%
“…Vaginal self‐sampling is feasible and acceptable as an alternative to improve attendance in cervical cancer screening . In comparison, urine collection is noninvasive, more convenient, easy to do, and less clinician‐dependent . Several studies implied its potential usage in the surveillance of the impact of the HPV prophylactic vaccine in adolescents, research on HPV and related diseases in men, and cervical cancer screening in pregnant women .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In comparison, urine collection is noninvasive, more convenient, easy to do, and less clinician-dependent. 3,9,10 Several studies implied its potential usage in the surveillance of the impact of the HPV prophylactic vaccine in adolescents, research on HPV and related diseases in men, and cervical cancer screening in pregnant women. [11][12][13][14][15][16] Additionally, urine-based testing has been shown to be flexible and promising in cervical cancer screening in referral population, [17][18][19][20] but the findings have not been demonstrated in screening practice.…”
mentioning
confidence: 99%